Multi‐wavelength, handheld laser speckle imaging for skin evaluation. Issue 4 (24th November 2020) - Zieger, Michael; Kaatz, Martin; Springer, Steffen; Riesenberg, Rainer; Wuttig, Andreas; Kanka, Mario; Stanca, Sarmiza; Reble, Carina; Khazaka, Georg; Sieg, Robin; De Gregorio, Marco; Sattler, Martin; et al.
Abstract: Objective: A handheld device was developed and qualified for in vivo human skin evaluation using laser speckle imaging technology. Methods: Each laser speckle device prototype allows the choice of up to three different laser wavelengths in the range of 400 nm to 800 nm in total. Speckle pattern analysis gives various speckle parameters, for example, speckle contrast, speckle size, speckle modulation or fractal dimension. The developed laser speckle device prototypes were evaluated investigating three skin issues. Results: We receive reproducible results from the speckle imaging device. For skin ageing, we found significant changes within three age groups. The effect of a methyl nicotinate treatment was clearly visible and quantifiable using a moorFLPI device as well as our speckle imaging device. In terms of basal cell carcinoma diagnosis, we found significant differences between normal and diseased skin, even though the number of samples was limited. Conclusion: As shown with first application examples, it was possible to demonstrate the potential of the method for skin evaluation in vivo.